Cinema em Goiás: quando tudo começou... (1960-1970) - Silva, Túlio Henrique Queiroz e (2018)
This work has as main purpose the study on the trajectory of the three artists from Goiás pioneers in cinematographic production in this state, being them: Cici Pinheiro, João Bennio e Jocelan Melquíades de Jesus; and also of the film analysis of five works carried out to Bennio and Jocelan M. Jesus. For this purpose, we used the methodology of film analysis highlighting some cinematographic elements in the Works to the extent that they allow us to compare them with other cinematographic productions and cinematic movements, besides the studies of the artistic trajectories of each personality approached. The films analyzed are from the 1960s and 1970s, being: O Diabo Mora no Sangue (1966), Tempo de Violência (1969), both produced by Bennio; Simeão, o Boêmio (1970), O Azarento, um Homem de Sorte (1973), directed and produced by Bennio; and A Fraude (1968), directed pby Jocelan Melquíades de Jesus. It is noteworthy that the pioneering work of Cici Pinheiro, O Ermitão de Muquém (1966), did not get finalized and for that reason we stopped in the artistic trajectory of Pinheiro until its first attempt of cinematographic production. . Through these analyzes it was possible to understand the “schools” from which these films were influenced, and also influenced, therefore, how this research will demonstrate, a series of artists that were consecrated in the Brazilian audiovisual market later were directly involved with some of these projects analyzed, as was the case with Cecil Thiré, who made his debut as a film diretor in O Diabo Mora no Sangue, as well as Carlos Reichenbach who directed the photography of A Fraude, among others.